The plastid cysteine synthase complex regulates ABA biosynthesis and stomatal closure in Arabidopsis - Sun, Shengkai; Ahmad, Nisar; Callenius, Hannah; Rajab, Hala; Uslu, Veli Vural; Cruz Cruz, José Rey; Zhao, Fang-Jie; Wirtz, Markus; Hell, Rüdiger (Nature Communications, 2025)
Global warming intensifies drought and high light stress periods, causing severe water loss and decreased crop yield. The phytohormone abscisic acid (ABA) is the dominant signal governing stomatal closure and water loss. Here, we uncover three signaling axes triggered by soil dehydration and high light stress converging on the dynamic assembly of the cysteine-synthase-complex in chloroplasts (pCSC). We show that pCSC assembly triggers ABA biosynthesis and stomatal closure in response to the soil-drying signals, sulfate (axis 1) and CLE25 (axis 2), and the high light-induced oxylipin OPDA (axis 3). Loss of the pCSC increases sensitivity to soil-drying and impairs high light-induced stomatal closure. Our findings uncover that the dynamic assembly of the pCSC acts as a sensor hub, integrating local and long-distance stress signals to promote stomatal closure by supplying cysteine for ABA biosynthesis in guard cells. We applied this knowledge to generate a soil-drying resilient plant showing no growth penalty.
Gesehen am 02.12.2025